Kumala Sari Rambe PENYULUHAN TENTANG YOGA PRENATAL PADA IBU HAMIL TM II DI PMB Bd. DERMINA TANJUNG, S.Tr.Keb - Kumala Sari Rambe (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
A healthy pregnancy is highly coveted by pregnant women, to be able to have a healthy pregnancy, pregnant women can do yoga exercises. An old method that is still used in pregnancy services is pregnancy exercise, where pregnancy exercise is also a method of relaxation and exercise for pregnant women which is a regular program in antenatal care, aiming to make pregnant women mentally and physically ready for the birth process.The objectives of implementing this community service are: Increasing interaction and sharing experiences between participants (pregnant women and pregnant women) and between pregnant women and health workers/midwives. Increase the understanding, attitude and behavior of pregnant women about: yoga exercises, body changes and complaints, pregnancy care, childbirth.Prenatal class participants are mothers at more than 20 weeks' gestation, because at this gestational age the mother's condition is strong and she is not afraid of miscarriage. Husbands/families are expected to attend prenatal classes at least 1 meeting. The implementation of this community service is carried out at PMB Bd. Dermina Tanjung, S.Tr.Keb, in the form of: weighing, measuring blood pressure, physical examination during pregnancy, counseling about the needs of pregnant women, yoga exercises